Biosorption of Cd2+, Cu2+, Ni2+, Pb2+ by four different macroalgae species (Costaria costata, Hizikia fusiformis, Gracilaria verrucosa, and Codium fragile) - Kang, J. K.; Pham, B. N.; Lee, C. G.; Park, S. J. (International Journal of Environmental Science and Technology, 2023)
This study used four different macroalgae (Costaria costata, Hizikia fusiformis, Gracilaria verrucosa, and Codium fragile) as biosorbents to remove the heavy metals, Cd2+, Cu2+, Ni2+, and Pb2+. Among the studied macroalgae, Costaria costata showed the best biosorbent activity for heavy metal removal. A Fourier transform infrared spectroscopy analysis indicated that the cell wall structure of Costaria costata has various functional groups such as amine, sulfonate, negatively charged hydroxyl groups, and carboxyl groups. The modification of Costaria costata using HCl and NaOH was ineffective in terms of improving its biosorption capacity. The kinetic experiments and modeling data showed reaction ratios in the following descending order: Ni2+ > Cd2+ > Cu2+ > Pb2+. Additionally, the Freundlich model was able to describe the equilibrium data well except for Pb2+. The maximum heavy metal adsorption capacity for Pb2+ was 160.990 mg/g; this was higher than the other heavy metals: 45.094, 44.768, and 42.082 mg/g for Cu2+, Cd2+, and Ni2+, respectively. This means that the adsorption of heavy metals onto Costaria costata occurred via covalent bonding as opposed to electrostatic attraction. Moreover, metal biosorption by Costaria costata enhanced significantly as the initial solution pH increased from 2 to 4. Among the competing cations, Al3+ demonstrated the greatest inhibitory effect on heavy metal removal because of its high charge valence and affinity. Consequently, the dried biomass of Costaria costata could be used to potentially eliminate heavy metals from aqueous solutions due to its characteristic high efficiency, easy acquisition, low cost, and easy preparation.
Keywords: Biosorbents; Carboxyl groups; Cell wall structure; Costaria costatum; Gracilaria; Heavy metal removal; Hydroxyl groups; Macro-algae; Negatively charged; Sulphonates; Biosorbent; Biosorption; Costaria costata; Heavy metals; Macroalgae